Empowering Women Through Religious Education Based on Local Wisdom - Ima Maisaroh; Sholeh Hidayat; Fadlullah Fadlullah (International Journal of Nusantara Islam, 2026)
This study aims to analyze women’s empowerment through religious education based on local wisdom in majelis taklim, a form of nonformal Islamic education, thereby enhancing women’s religious, social, and cultural capacities within the community. Majelis taklim functions not only as a venue for religious learning but also as a space for social transformation of women through the internalization of Islamic values and local cultural norms prevalent in society. The research employs a qualitative ethnopedagogical approach to understand the learning processes, cultural values, and religious education practices within majelis taklim activities. Data were collected through observations, in-depth interviews, and documentation involving administrators, female religious teachers (ustazah), and female members of the majelis taklim. Data analysis was conducted through data reduction, data presentation, and thematic conclusion drawing. The results indicate that local-wisdom-based religious education in majelis taklim plays a crucial role in women’s empowerment, particularly in enhancing religious understanding, strengthening religious character, fostering social solidarity, and developing women’s capacity to fulfill social and familial roles. Local values such as gotong royong (mutual cooperation), deliberation, community religious traditions, and mutual respect are integrated into the learning process, creating a contextual and easily accepted educational model for participants. Furthermore, majelis taklim serves as a medium for reinforcing Muslim women’s identity, enabling them to adapt to social changes without abandoning cultural values or Islamic teachings. The study concludes that local-wisdom-based religious education in majelis taklim represents an effective model of women’s empowerment, fostering sustained religious, social, and cultural awareness in the community.